PEDAGOGICAL OPPORTUNITIES OF INDEPENDENT LEARNING IN MUSIC EDUCATION FOR STUDENTS’ SELF-DEVELOPMENT - Bobokulova Moxinur Jamshid qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article examines the pedagogical opportunities of independent learning in music education for fostering students’ self-development. The study explores how independent learning strategies, including digital resources, interactive methods, and project-based activities, contribute to enhancing students’ technical skills, creative abilities, and reflective thinking. The article highlights the role of self-directed study in promoting autonomy, motivation, and personal growth, and emphasizes the teacher’s role in guiding and supporting independent learning. The findings indicate that independent learning in music education not only strengthens practical and theoretical competencies but also cultivates lifelong learning habits and professional readiness.